The Effect Of Product Quality On Customer Satisfaction At The Fajar Building Shop, Topoyo Sub-District, Mamuju District, West Sulawesi Province - Fadil, M.; Pasigai, Moh Aris; Nurlina, Nurlina (Economos : Jurnal Ekonomi dan Bisnis, 2025)
The Influence of Product Quality on Customer Satisfaction at Fajar Shop, Building, Topoyo District, Mamuju Regency, West Sulawesi" Thesis for Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Makassar. This study aims to examine the effect of product quality on customer satisfaction at the Fajar Building Shop, Topoyo District, Mamuju Regency, West Sulawesi. This study uses primary data sources, where researchers distribute questionnaires to 45 customers of Fajar Bangunan Store. The analysis technique in this research is validity test, reliability test, classical assumption test, and hypothesis testing through simple linear regression analysis test and T test. Partially, the results of this study indicate that product quality has a positive and significant effect on customer satisfaction at the Fajar Building Shop, Topoyo District, Mamuju Regency, West Sulawesi, which is indicated by the T arithmetic value of 2.041 > T table value of 2.018 and a significance value of 0.047 < 0.05. So the first hypothesis is accepted.